VOLUME 5, NO 2 (2017) - Editor In Chief (ARO-The Scientific Journal of Koya University, 2017)
Dear readers, Aro-the Scientific Journal of Koya University is closing its ninth issue (Vol V, No 2, 2017) after an exciting yet dynamic season of valuable inputs by our research community and supportive reviewers. Aro is publishing its 4th issue as an internationally listed Scientific Journal in Kurdistan Region of Iraq. Notably, Aro has been accepted for indexing in the Emerging Sources Citation Index (ESCI), a new edition of Web of Science™ as of Feb 2016. Content in this index is under consideration by Thomson Reuters to be accepted in the Science Citation Index Expanded™ (SCIE). Aro’s individual articles are currently listed by Thomson Reuters using articles unique DOI numbers which is a historical achievement for our academic community. Aro is ending its fifth year journey in leading the quality of regional scientific publications with global impact. The editorial team has been working tirelessly to keep the novel mission and sustain Aro’s future publications with greater impacts and citations. It is exciting that Aro has been awarded to DOAJ Seal listing which is an indication of a trusted high standard open access scientific work that so far haven allocated to 88 journals worldwide only. The upcoming new season will be an even more exciting period in Aro’s life as Thomson Reuters will examine our journal for full permanent listing.